Da ambivalência e magnitude técnica à necessidade de uma nova ética na filosofia jonasiana - Orcheski, Adaiana Pinto (2015)
It is intended to show in this thesis how the concept of technique changes in accordance with the historical background. Besides, it also provides clues to think about the premises of technological civilization in its unprecedented and emerging context from the thought of Hans Jonas. As a result, we will be analyzing the notion of formal and substantial dynamics of technical and intrinsic problems related to them, such as the changes that the technique has been undergone over the years; in ancient times, the changes occurred slowly and in balance, along the time, they turned into power and end in itself. The jonasiana philosophy will contribute to determine, in the case of the technique, the impacts on the lives and understand when and how to become objects of it. Accordingly, as realizing that the technique does not have its own ethics dynamics, we will try to follow Jonas´ advice, signaling some assumptions and ways for an ethics of technique so that means that they can be found in order to save future lives and overcome anthropocentrism. This leads then, to the notion of magnitude and technical ambivalence, notions that concern the technical power, which leads us to uncertain, meaning risks and, even when intentions are good, they can lead us to threats. In this context, it is the moral ambivalence, the need to be aware of both good and bad potential of our action. The magnitude emerged is the cumulative nature of the technical issues where harmful effects spread throughout the planet, affecting even future generations and, at worst, precluding the opportunity to reverse its damage. The magnitude and technical ambivalence reach prominent place these days and hence; the demand of technique humanization can be effective on them. Thereby acting in response to the effects of the technique at present and possible future disasters, Jonas requires technical ethics.